INVESTIGATING THE FORMS IN ENGLISH - Zulprianto Zulprianto (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
The use of <lNG> form is enormously extensive in English and possibly, poses some conceptual or grammatical difficulties for English teachers and learners. On the one hand, <lNG> morpheme is attached to a verbal base resulting in a verbal form and function. Such form and function can be assumed to be the default case. On the other hand. <lNG> morpheme can also be attached to a verbal base, but brings about adjectival and nominal functions. ln relation to such usages of <lNG>. Nida (1949) suggests that <lNG> should simply be treated as a single morpheme with various usages. As a matter of fact, despite being used as a noun or adjective, <lNG> forms still keep their verbal force. The case of <lNG> forms uncovers the point where word-class indeterminacy exists and therefore they are prevailingly regarded as trans categorial, a sort of 'hybrid category' and'seem to be core members of more than one category, simultaneously (Alexiadou 2013; Malouf 1996). This paper has trvo objectives: firstly, to elaborate the idiosyncrasies of <lNG> forms which are certainly valuable for English teaching and learning and, secondly. to examine the distributions of <lNG> forms in a small English narrative corpus by employing a quantitative analysis.